The role of non-verbal communication in the development of intercultural competence in students of philological faculties or future translators - Curkan-Dróżka, Ełona (Вопросы семантики и стилистики текста: лингвистический дискурс, 2021)
The article presents the importance of shaping intercultural competence in teaching a foreign language in philological studies also in translation specialization. The author focuses on one aspect of this complex concept, namely non-verbal communication. She also considers it necessary to familiarize students with the specificity and cultural dependence of non-verbal means, which constitute an important part of the professional preparation of students. The article presents selected methods of introducing non-verbal means of communication during classes.